THE CONTRIBUTION OF FACULTATIVE ACTIVITIES - HANDBALL IN TRANSFORMATION OF MOTORIC STATUS OF THE FEMALE STUDENTS OF THE FIRST GRADE OF SECONDARY SCHOOL - Živorad Marković; Dragoljub Višnjić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The research was done with the aim of identifying the contribution of facultative activities in transformation of motoric status of female students of the fi rst grade of secondary school. The research was carried as a pedagogical experiment - of longitudinal character, on the specimen of 67 girls of Agricultural-veterinary school with the boarding school "Svilajnac" in Svilajnac during the 2005/2006 school year. For the estimation of the motoric status fi ve standardized movement tasks were applied: long jump from the spot; hanging; a 20 meter running with a fl ying start; slalom with three medicine balls; and standing on one foot on the bench. For processing of data which were got by empirical research, apart from the procedures of descriptive statistics, another thing was applied: multivariant analysis of covariance and univariant analysis of covariance. Positive effects of facultative activities have made statistically signifi cant changes between control and experimental group on the fi nal measurement in four from fi ve variables. Statistically insignifi cant changes were in standing on one foot on the bench